Recognizing and Addressing Workplace Anxiety: Strategies for Better Mental Health - Yuniar Sari, Niken; Kadri, Mohd.; Nuryuliati; Rahmadani, Zulia; Safira S, Risma; Putri, Rahmia; Aulia, Nurul; Putri Khairul, Sy. Aurora; Rohimi, Siti; Fernanda, Nurriza Rizky; Putri, Napisya; Herlina, Herlina (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2025)
Poor mental health can reduce employee job satisfaction and increase the risk of burnout. When employees are not feeling well mentally, they are more likely to experience burnout, which can lead to high employee turnover. This activity aims to increase workers' understanding of workplace anxiety and provide effective strategies for managing and overcoming the problem, in order to support better mental health. This activity uses lecture methods, interactive discussions, questions and answers and demonstrations or role plays of deep breathing techniques. The counseling went well and according to plan. Participants were very enthusiastic about participating in the counseling and actively participated in the discussion. After the participants did the technique taught, namely deep breathing relaxation, the participants looked more relaxed. It is hoped that the deep breathing relaxation technique is effective as a distraction from anxiety from the participants who attended.